2010
DOI: 10.1007/s10565-010-9158-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of oxidative stress in signaling and inflammation induced by particulate matter

Abstract: This review reports the role of oxidative stress in impairing the function of lung exposed to particulate matter (PM). PM constitutes a heterogeneous mixture of various types of particles, many of which are likely to be involved in oxidative stress induction and respiratory diseases. Probably, the ability of PM to cause oxidative stress underlies the association between increased exposure to PM and exacerbations of lung disease. Mostly because of their large surface area, ultrafine particles have been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(87 citation statements)
references
References 229 publications
(275 reference statements)
4
81
0
2
Order By: Relevance
“…Since air particulates can provoke oxidative stress and an inflammatory response in the lung and heart,57 oxidative stress is a potentially important cellular mechanism. A study by Schwartz et al 58 concluded that the effects of PM 2.5 on HF seemed to be mediated by reactive oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Since air particulates can provoke oxidative stress and an inflammatory response in the lung and heart,57 oxidative stress is a potentially important cellular mechanism. A study by Schwartz et al 58 concluded that the effects of PM 2.5 on HF seemed to be mediated by reactive oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress results from an imbalance between the formation of reactive oxygen species (ROS) and the ability of the organism to readily detoxify the reactive intermediates or to repair the resulting damage (Mazzoli-Rocha et al, 2010). Oxidative damage to cellular macromolecules (nucleic acid, lipids and proteins) is associated with the development of cancer, respiratory tract and cardiovascular diseases (Yang and Omaye 2009), neurodegenerative diseases (Andersen 2004) as well as ageing (Evans et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…47 A reason for lung cell (such as epithelial and macrophage) activation and damage following PM exposure is via oxidative stress pathways. 48 Tuder and colleagues 49 have shown that apoptosis predominates in lung regions of oxidative stress. We postulate that the reduction in the volume fraction of PM in lung tissues in subjects with severe COPD is due to apoptosis 44,47 of these tissues, possibly due to the burden of PM in these tissues.…”
Section: Discussionmentioning
confidence: 99%